Behaviour of RC slabs due to reinforcement corrosion - Kumar, S. Sundar; Bharatkumar, B. H.; Krishnamoorthy, T. S.; Ramesh, G.; Lakshmanan, N. (Journal of Structural Engineering, 2025)
Corrosion is a world wide problem which has severe implication on the growth and development of mankind. Studies indicated that the total cost of corrosion on global economy including both direct and indirect costs is around 1.9 trillion (USD) annually that is around 3.8 percent of world GDP. In India the cost of corrosion is around 1.5 lakh crore per annum. The common findings of corrosion studies undertaken by several countries is that the annual corrosion costs range from approximately 1 to 5 percent of the GDP of each nation. Apart from the economic aspect it is one of the major durability problems in RC structures. Corrosion in reinforcement occurs mainly when it is exposed to the chlorides. Carbonation of concrete, or penetration of acidic gases into the concrete, being other causes of reinforcement corrosion. Slabs form one of the main structural elements which are highly prone to corrosion as they are of smaller thickness and usually provided with little cover. This paper presents the results of the experimental studies conducted on reinforced concrete slabs of dimension 2x2 m and a thickness of 60 mm. A total of five specimens were tested. Corrosion in two specimens were accelerated by impressed current technique, two slab specimens were cast with corroded reinforcement and compared with control slab.